Terpaan Berita Tentang Gangguan Jaringan IndiHome dan Brand Image di Twitter Terhadap Tingkat Kepercayaan Konsumen Mengenai Layanan IndiHome - Georgina Inessa Zephira; Djoko Setyabudi; Muchamad Yuliyanto (Interaksi Online, 2021)
The arrival of the Covid-19 pandemic has had a negative impact on society in various fields, but not for the digital service industry. During the pandemic, all residents are urged by the government to reduce all activities outside home, including work and study purposes. The term Work From Home (WFH) is often mentioned in the news and among the public. During the Work From Home era, the need for digital services such as wi-fi increased. However, IndiHome unfortunately experiences network disruptions for several times within a certain period of time wich provokes negative comments and complaints from consumers on Twitter. This study was conducted with the aim of knowing how much influence the news exposure about IndiHome’s network disruptions and brand image on Twitter had on the level of consumer’s confidence in IndiHome’s services. When the need for internet is increasing rapidly. The theory used in this research is New Media Theory and e-Word of Mouth Theory with a non-probability sampling technique, a sample of 100 people, male and female, aged 16-64 years and have been exposed to the news about IndiHome’s network disruptions during the pandemic. The test for both hypothesis show that there is an influence between news exposure about IndiHome’s network disruption and brand image on Twitter on the level of consumer’s confidence in IndiHome’s services with a significance value of 0,000.